GINGIVAL RECESSION IN RELATION TO MUCOGINGIVAL DEFORMITIES AND OTHER PREDISPOSING FACTORS AFFECT FEMALES IN LOWER ESTHETIC ZONE - Al-Hajri, Manal M.; Al-Kadasi, Baleegh A.; Al-Wesabi, Mohammed A.; Aldeen, Haifa M. Sharaf; Al-Rai, Sarah (Universal Journal of Pharmaceutical Research, 2022)
Background: Gingival recession (GR) is one of the most common esthetic problems affecting the middle and older aged peoples. GR can lead to many changes as root caries, hypersensitivity, erosions, abrasions, plaque retention and aesthetic dissatisfaction. This study aimed to evaluate the prevalence of gingival recession in relation to mucogingival deformities in lower esthetic zone. Methods: A cross-sectional study was done on a sample of 290 females. The participants were interviewed for personal habits and examined for intraoral distribution of gingival recession and its various predisposing factors. Results: The prevalence of gingival recession in lower anterior teeth was 234, 80.69 %.Around half of the participants had Millers' class I GR (n=146, 49%), thin gingival phenotype (n=168, 56.9 %), mucosal and gingival labial frenum attachment(n=132, 44.7%, n=148, 50.2%). Most of the participants had a sufficient attached gingiva (n=246, 83.4%) and normal vestibular depth(n=278, 94.2%). GR were statistically significant with vestibular depth, gingival biotype and attached gingiva (P≤0.05). Conclusion: Gingival recession in lower aesthetics zone was high in females especially Miller class I gingival recession due to thin gingival phenotypes. Most of Yemeni females have adequate attached gingiva, normal vestibular depth with a frequent mucosallabial frenum in lower anterior teeth. Peer Review History: Received: 3 August 2022; Revised: 10 September; Accepted: 18 October; Available online: 15 November 2022 Academic Editor: Dr. A.A. Mgbahurike , University of Port Harcourt, Nigeria, amaka_mgbahurike@yahoo.com Reviewers: Dr. Bilge Ahsen KARA, Ankara Gazi Mustafa Kemal Hospital, Turkey, ahsndkyc@gmail.com Dr. George Zhu, Tehran University of Medical Sciences, Tehran, Iran, sansan4240732@163.com